2017
DOI: 10.1016/j.conbuildmat.2017.03.066
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle analysis of environmental impact vs. durability of stabilised rammed earth

Abstract: Rammed earth (RE) has enjoyed a revival in recent decades due to the increasing awareness of environmental issues surrounding the building industry. Although RE in its traditional form is deemed a highly environmentally-friendly material, the same cannot be said for its modern stabilised counterpart. Comprehensive experimental procedures exist to estimate mechanical strength properties of stabilised RE (SRE). However, tests for material durability are far less common. Engineers and practitioners therefore assu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
100
0
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(114 citation statements)
references
References 27 publications
2
100
0
12
Order By: Relevance
“…Several research investigations have recently been conducted to study the properties of RE: mechanical characteristics [1,[11][12][13][14][15][16][17], durability [9,18], hygrothermal behavior [6,[19][20][21], and earthquake performance [22][23][24][25]. However, using nondestructive techniques to determine the in-situ characteristics of RE walls is less reported, although several studies can be cited.…”
Section: Introductionmentioning
confidence: 99%
“…Several research investigations have recently been conducted to study the properties of RE: mechanical characteristics [1,[11][12][13][14][15][16][17], durability [9,18], hygrothermal behavior [6,[19][20][21], and earthquake performance [22][23][24][25]. However, using nondestructive techniques to determine the in-situ characteristics of RE walls is less reported, although several studies can be cited.…”
Section: Introductionmentioning
confidence: 99%
“…The use of alternative building materials and techniques such as the vernacular ones (rammed earth, adobe, traditional vaults, etc.) can reduce environmental impacts, as shown by several studies (Praseeda et al, 2014) (Arrigoni et al, 2017;Christoforou et al, 2016;Meli a et al, 2014;Sanz-Calcedo et al, 2012;Shukla et al, 2009;Venkatarama Reddy and Jagadish, 2003). Beyond the environmental advantages, Morel et al (2001) and Ramesh (2012) also concluded that using local materials has socioeconomic benefits, such as to reduce the cost of construction and to foster local economies by paying the cost of the materials and labour locally.…”
Section: Vernacular Materials Versus Conventional Materialsmentioning
confidence: 97%
“…To change this reality, several authors (Arrigoni et al, 2017;Cabeza et al, 2013;Chel and Tiwari, 2009;Morel et al, 2001;Ramesh, 2012;Shukla et al, 2009;Venkatarama Reddy and Jagadish, 2003) have focused their attention on researching alternatives to current building technologies. Some of these "alternatives" are, in fact, traditional or vernacular construction technologies used by communities for centuries.…”
Section: Vernacular Materials Versus Conventional Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these impact categories, the reason of decreased GWP should be the preperation of raw materials and usage of fuel in production stage. As previously discussed, environmental performance was seriously influenced by the manufacture of HPMs and transportation …”
Section: Resultsmentioning
confidence: 96%